You can start to consider this as a straightforward double decomposition reaction:

H2SO4(aq) + Li2SO3(aq) → H2SO3(aq) + Li2SO4(aq)

But this cannot be a reaction because all products are (aq) as well as all reactants are (aq) , At this point check on the requirements for a double decomposition reaction. You will find that this does not comply with these requirements.

What happens in reality is that the “compound” H2SO3 breaks down to produce H2O and SO2

Now you can write a reaction equation:

H2SO4(aq) + Li2SO3(aq) → Li2SO4(aq) + SO2(g) + H2O(l)

Then the ionic equation is:

2H+(aq) + SO4 2-(aq) + 2Li+(aq) + SO3 2-(aq) → 2Li+(aq) + SO4 2-(aq) + SO2(g) + H2O(l)

And the net ionic equation is:

2H+(aq) + SO3 2-(aq) → SO2(g) + H2O(l)

Leave a comment